2016
DOI: 10.1007/s13364-016-0298-5
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of two syntopic and closely related aerial-hawking bat species during breeding season in Białowieża Primaeval Forest

Abstract: Temporal and spatial activity of bats is species specific and shaped by many factors such as energy requirements, climate conditions and food distribution. Pregnancy and lactation are the most energy-demanding periods throughout the female life cycle. During these periods, females have to optimize their activity patterns to maximize foraging success; however, they simultaneously need to take care of their young. In addition, daily and seasonal fluctuations of insect availability strongly affect bat foraging ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 72 publications
(95 reference statements)
4
8
0
Order By: Relevance
“…Generally, bats were most often present and acoustically active just after sunset, and activity was decreasing toward midnight. This result generally confirms earlier findings concerning temporal variation of bat activity, which can be driven by both insect biomass and air temperature (Hayes, 1997;Ruczy nski et al, 2017). Also, more bats were recorded later in the season which may be associated with the appearance of newly weaned juveniles (Ciechanowski et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Generally, bats were most often present and acoustically active just after sunset, and activity was decreasing toward midnight. This result generally confirms earlier findings concerning temporal variation of bat activity, which can be driven by both insect biomass and air temperature (Hayes, 1997;Ruczy nski et al, 2017). Also, more bats were recorded later in the season which may be associated with the appearance of newly weaned juveniles (Ciechanowski et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…However, M. bechsteinii reached the end of its activity period an average of 12 min sooner than N. leisleri (Table 3). These results are generally in line with previous observations of the activity patterns of N. leisleri (Ruczyński et al 2017, Shiel et al 2007. No comparable studies exist for M. bechsteinii, but in acoustic studies with results reported at the genus level all-night activity was determined for Myotis (Perks & Goodenough, 2020).…”
Section: Species Comparisons Of Circadian Activitysupporting
confidence: 93%
“…3), particularly in relation to niche partitioning responses. As a special case of phenotypic plasticity (Dingemanse et al 2010), niches of potential competitors such as ecomorphologically similar bat species may be partitioned in sympatry by choosing different prey (Arlettaz 1999), habitats (Salsamendi et al 2012), or activity time (Ruczyńki et al 2017, Schimpp et al 2018), whereas such behaviours would differ under allopatric competitive release and permit niche expansion. For example, greater and lesser mouse-eared bats Myotis myotis and Myotis blythii are thought to avoid competition by using different habitats and feeding on different staple prey.…”
Section: Echolocation and Wing Morphologymentioning
confidence: 99%